2018
DOI: 10.1093/nar/gky128
|View full text |Cite
|
Sign up to set email alerts
|

Human CHD1 is required for early DNA-damage signaling and is uniquely regulated by its N terminus

Abstract: CHD1 is a conserved chromatin remodeling enzyme required for development and linked to prostate cancer in adults, yet its role in human cells is poorly understood. Here, we show that targeted disruption of the CHD1 gene in human cells leads to a defect in early double-strand break (DSB) repair via homologous recombination (HR), resulting in hypersensitivity to ionizing radiation as well as PARP and PTEN inhibition. CHD1 knockout cells show reduced H2AX phosphorylation (γH2AX) and foci formation as well as impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…As a result it is somewhat surprising that the area of contact between the chromodomains and DNABD is so small. It is possible that additional regions of Chd1 including the Nterminus that is not resolved in the density map also contribute to this interaction as suggested by previous studies of Chd1 proteins (Liu et al, 2015;Zhou et al, 2018) (Sundaramoorthy et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…As a result it is somewhat surprising that the area of contact between the chromodomains and DNABD is so small. It is possible that additional regions of Chd1 including the Nterminus that is not resolved in the density map also contribute to this interaction as suggested by previous studies of Chd1 proteins (Liu et al, 2015;Zhou et al, 2018) (Sundaramoorthy et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…PARP1, CHD2, and H3.3 regulate the assembly of NHEJ complexes at broken chromosomes to promote efficient DNA repair (Luijsterburg et al, 2016). Targeted disruption of the CHD1 gene in human cells leads to a defect in DSB repair via homologous recombination, resulting in hypersensitivity to ionizing radiation and in increased error-prone NHEJ repair for DSB repair (Kari et al, 2016;Shenoy et al, 2017;Zhou et al, 2018). We have shown that null mutations of Drosophila Chd1 cause hypersensitivity to ionizing radiation at the third instar larval stage, suggesting that Drosophila CHD1 is also involved in DSB repair.…”
Section: Itroductionmentioning
confidence: 90%
“… 2018 ; Zhou et al. 2018 ). In the present study, we observed histone H2A release from chromatin after empty vector-transfected and mutant BRG1-transfected cells were treated with ETO ( Figure 3 (B)).…”
Section: Discussionmentioning
confidence: 99%